Differential Ablation of Organic Coatings From Micrometeoroids Simulated in the Laboratory. Issue 4 (20th April 2022) - DeLuca, Michael; Sternovsky, Zoltan; Armes, Steven P.; Fielding, Lee A.; Horányi, Mihály; Janches, Diego; Kupihar, Zoltan; Munsat, Tobin; Plane, John M. C.
Abstract: Micrometeoroids contain organic material that may undergo differential ablation during atmospheric entry, potentially depositing organic material into Earth's atmosphere and affecting the radar detectability of meteors. To investigate the differential ablation of organics, we used a dust accelerator to shoot submicron polypyrrole‐coated olivine particles at speeds of 10–20 km/s into a gas target containing air. A set of biased electrodes placed along the path of the particles measured the charges generated when the particles ablated and the ablated molecules collided with gas molecules. We observed that the particles differentially ablate their organic polypyrrole coatings prior to their inorganic olivine cores, producing spikes in charge production, with charge yields of 10 4 –10 5 C/kg even at relatively low speeds. These measurements suggest that large organic molecules survived ablation and are responsible for the observed charge production since small molecules either do not produce ions at those speeds or produce them in much lower quantities than observed. We modeled the ablation using basic meteor physics by assuming that the polypyrrole coating decomposes into pyrrole monomer. Extending these results to the ablation of micrometeoroids in the atmosphere indicates that organic coatings should ablate at high altitudes within relatively narrow altitude ranges, which has consequences for the detectability of meteors by radar. Since the ablated coatings generate relatively large molecules, the results also suggest that micrometeoroids can deliver complex organic material into planetary atmospheres by ablating them during entry, potentially serving as a source of prebiotic organics. Plain Language Summary: Micrometeoroids entering the atmosphere heat up due to collisions with gas molecules and lose mass through ablation. The more volatile components ablate before the less volatile components, a process called differential ablation. To study how volatile organics in micrometeoroids will ablate, we shot olivine particles coated in polypyrrole, an organic conducting polymer, into a gas target at speeds of 10–20 km/s. The particles differentially ablated their polypyrrole coatings and produced charges when the ablated molecules collided with gas molecules. Using a set of electrically biased charge collectors located inside the target, we found that the coatings produced large amounts of charge, which suggest that large molecules survived ablation. This is because small molecules and atoms do not have the kinetic energy to produce ions when they collide with gas molecules. We modeled the process by assuming that the polypyrrole coating degrades to form pyrrole monomer. Our measurements suggest that organics ablated from micrometeoroids may produce sufficient charge to be detectable by radar. The apparent large size of the ablating molecules also suggests that meteors may be able to deliver complex organics into the atmosphere that could have been useful building blocks for life on the early Earth. Key Points: Using a dust accelerator, we shot polypyrrole‐coated olivine particles at 10–20 km/s into a gas target containing air The particles differentially ablated their organic coatings in the form of large molecules The results suggest that meteors may deliver complex organics into planetary atmospheres and those organics may produce detectable charges